Impact of Economic Constraints on Public Health Delivery Systems Structures - Smith, Sharla A. (Am J Public Health, 2015)
Objectives. We estimated the effect of economic constraints on public health delivery systems (PHDS) density and centrality during 3 time periods, 1998, 2006, and 2012. Methods. We obtained data from the 1998, 2006, and 2012 National Longitudinal Study of Public Health Agencies; the 1993, 1997, 2005, and 2010 National Association for County and City Health Officials Profile Study; and the 1997, 2008, and 2011 Area Resource Files. We used multivariate regression models for panel data to estimate the impact of economic constraints on PHDS density and centrality. Results. Findings indicate that economic constraints did not have a significant impact on PHDS density and centrality over time but population is a significant predictor of PHDS density, and the presence of a board of health (BOH) is a significant predictor of PHDS density and centrality. Specifically, a 1% increase in population results in a significant 1.71% increase in PHDS density. The presence of a BOH is associated with a 10.2% increase in PHDS centrality, after controlling for other factors. Conclusions. These findings suggest that other noneconomic factors influence PHDS density centrality.